NiMoS-Modified Carbon Felt Electrode for Improved Efficiency and Stability in a Neutral S/Fe Redox Flow Battery - Dan Mei; Bowen Liu; Haiqing Ma; Zhaoguo Zhang; Fan Wu; Yanan Chen; Jawad Ali; Futang Xing; Liangbin Xiong (Molecules)
Polysulfide-ferricyanide redox flow batteries (PFRFBs) are gaining significant attention in long-duration energy storage for their abundant availability and environmental benignity. However, the sluggish kinetics of the polysulfide redox reactions have tremendously constrained their performances. To address this issue, we developed a NiMoS catalyst-modified carbon felt (NiMoS-CF) electrode, which significantly accelerates the electrochemical reaction rates and enhances the cycling stability of PFRFB. Our PFRFB system, integrated with the NiMoS-CF electrode, exhibited an energy efficiency of 70% and a voltage efficiency of 87%, with a remarkable doubling of its cycle life as opposed to the pristine carbon felt (CF) electrode at a current density of 40 mA cm−2. Notably, during 2500 cycles of charge–discharge testing, we achieved an average coulombic efficiency exceeding 99%. These improvements in PFRFB performance can be attributed to the NiMoS-CF electrode’s large surface area, low resistance, and robust redox activity. This study offerings a novel approach for enhancing the electrochemical reaction kinetics and cycling stability in PFRFBs, laying a scientific foundation in the applications of practical PFRFBs for next-generation energy storage.